European Conference and Exhibition on Optical Communication 2012
DOI: 10.1364/eceoc.2012.mo.2.c.5
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Cascaded In-Line Single-Pump Fiber Optical Parametric Amplifiers in Recirculating Loop Transmission

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…In [10] it has been experimentally shown that an OSNR penalty of less than 1 dB after amplification with PI-FOPA is achievable for 16-QAM signals provided that the output pump power is at least 17 dB larger than the overall output signal power. The experimental use of PI-FOPA as an inline amplifier for WDM systems has been demonstrated in [2,11].…”
Section: Ultimate Performance Of Pi-fopasmentioning
confidence: 99%
“…In [10] it has been experimentally shown that an OSNR penalty of less than 1 dB after amplification with PI-FOPA is achievable for 16-QAM signals provided that the output pump power is at least 17 dB larger than the overall output signal power. The experimental use of PI-FOPA as an inline amplifier for WDM systems has been demonstrated in [2,11].…”
Section: Ultimate Performance Of Pi-fopasmentioning
confidence: 99%
“…Some studies have demonstrated inline-amplified transmission with an HNLF-based OPA. With a single-channel signal, 4×80-km dispersion-managed transmission using a single-polarization 40-Gbps on-off keying modulated signal with the OPA compensating for the span-loss compensation of 20 dB has been reported [18]. With a WDM signal, inlineamplified transmission over 25.2-km single-mode-fiber (SMF) spans using a 20-ch 50-GHz-spaced WDM signal with 100-Gbps polarization-division-multiplexed (PDM)-quadrature phase shift keying (QPSK) signals has been reported [19]; its amplification bandwidth is 1 THz.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the OSNR degradation from the FOPA loss, as well as other added noise, overall system performance would have been improved by bypassing this FOPA completely. In another paper, multiple FOPA amplifications were performed for a single 40Gb/s DPSK signal transmitted within a recirculating loop containing 80km of SSMF [19]. This is the only previous demonstration of cascaded in-line FOPA amplification, but it was a non-PI architecture, and thus the pump and signal required manual polarization alignment and this would not be scalable to DWDM operation.…”
Section: Introductionmentioning
confidence: 99%